Analysis Mixed Traits of Jo March That Affect Her Gender Identity - Naura, Dania (English Department, Faculty of Humanities, Andalas University, 2023)
The objective of this research is to reveal and explain the mixed traits through Jo March character and to understand the impact that influence her gender identities. This research employs qualitative analysis method and applying the theory of Robert DiYanni character and characterization, gender stereotypes and sex role inventory which invented by Sandra Bem. This theory has a purpose to analysis the gender issues which contained in this film. The result shows that the main character, Jo March has the characterization of self-sufficient, brave and principled woman through DiYanni point of view. Moreover, the research discovered that Jo March adopts both mixed traits which is both masculinity and femininity traits in woman’s body that made them include to androgyny. Her masculinity traits are independent, strong personality, assertive and analytical, while her femininity traits are affectionate, compassion, sensitive and warm. This mixed traits that possessed in Jo breaks the stereotype that female character constantly depicted inferior role, however in this research it demonstrates that Jo not only dominate by masculine traits yet she balanced her feminine traits as well. In this context, it affects her relationship with Laurie, the male character by leads the relationship to frustration and regret between them.